IMPLEMENTASI PENANAMAN KARAKTER TANGGUNG JAWAB TUGAS SEKOLAH OLEH GURU PADA SISWA KELAS X SMK NEGERI 7 PONTIANAK - Asih, Astri; Rosyid, Rum; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe objective of this current study is to observe an effort to instill a sense of responsibility for assignments to students to be an ethical and responsible person. The conducted study is a qualitative research on the class X students of SMKN 7 Pontianak. The research data were collected using observation, interviews, and documentary study techniques. The instruments of data collection used were interview guides, observation guides, notes, and document archives. The findings showed that the efforts to teach a sense of responsibility to the students could be integrated into the learning process through spontaneous activities, that is, through modeling. Through modeling, students’ attitudes and behaviors are mostly determined by the teachers and other educational staffs’ attitudes and behaviors. To overcome the obstacles, i.e., disobedience of the task completion, the school gives the students to do the additional assignment given as a consequence. The school and teachers also conduct supervision and approach personally to students directly to find out the core problems faced by students.Keywords: Character Implementation, Sense of Responsibility, School Assignments, SMKN 7 Pontianak.